Environmental policy under model uncertainty: a robust optimal control approach - Michael Funke; Michael Paetz (Center for Economic Studies and ifo Institute (CESifo), 2007)
Model uncertainty is inherent in the design of optimal environmental policy. We investigate the consequences in a simple linear model, where the aim of the policymaker is to stabilize the carbon content of the atmosphere. We study how decision-makers' concerns about robustness alter policy using the Hansen and Sargent (2000, 2003, 2007) approach. The analysis shows that a policymaker, who fears model misspecification should react more aggressively to changes in the stock of atmospheric carbon and implement policies which deliver a greater reduction of emissions.
Keywords: C61; Q25; Q28; D81; 330; robust control model uncertainty; environmental policy; Umweltpolitik; Klimaschutz; Kontrolltheorie; Robustes Verfahren; Entscheidung bei Unsicherheit; Theorie